2018
DOI: 10.3390/ijms19113342
|View full text |Cite
|
Sign up to set email alerts
|

The Pathophysiology of Gestational Diabetes Mellitus

Abstract: Gestational diabetes mellitus (GDM) is a serious pregnancy complication, in which women without previously diagnosed diabetes develop chronic hyperglycemia during gestation. In most cases, this hyperglycemia is the result of impaired glucose tolerance due to pancreatic β-cell dysfunction on a background of chronic insulin resistance. Risk factors for GDM include overweight and obesity, advanced maternal age, and a family history or any form of diabetes. Consequences of GDM include increased risk of maternal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
914
3
50

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,117 publications
(1,164 citation statements)
references
References 166 publications
15
914
3
50
Order By: Relevance
“…However, the pathophysiology of GDM is similar to that involved in T2DM and not in T1DM. Additionally, around 70% of the patients with previous GDM develop T2DM later in life . Therefore, it seems to be more interesting to analyse whether the frequency of CD3 + TCRγδ in GDM is a risk marker for the development of T2DM.…”
Section: Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the pathophysiology of GDM is similar to that involved in T2DM and not in T1DM. Additionally, around 70% of the patients with previous GDM develop T2DM later in life . Therefore, it seems to be more interesting to analyse whether the frequency of CD3 + TCRγδ in GDM is a risk marker for the development of T2DM.…”
Section: Immune Cellsmentioning
confidence: 99%
“…Additionally, around 70% of the patients with previous GDM develop T2DM later in life. 35 Therefore, it seems to be more interesting to analyse whether the frequency of CD3 + TCRγδ in GDM is a risk marker for the development of T2DM. The role of neutrophils in reproduction remains unclear, but it has been shown that pregnancy is associated with a mild pro-inflammatory state, characterized by increased activation of these cells.…”
Section: Tcd4 Subpopulationsmentioning
confidence: 99%
“…This pathology represents approximately 80% of GDM cases, which are classified based on β‐cell dysfunction with previous history or worsening peripheral insulin resistance (Plows et al . ), indicating a diabetic disorder that includes aspects of all three major categories of the disease (Type I, Type II and other).…”
mentioning
confidence: 99%
“…As pregnancy progresses, the surge of pregnancy hormones including prolactin, progesterone and placental lactogen promote a temporary state of mild insulin resistance, allowing blood glucose to remain high and supply the fetus via the placenta (Plows et al 2018). Maternal placental hormones then trigger a response in pancreatic β-cells to attempt to restore euglycaemia -β-cells and often α-cells of the pancreas undergo hypertrophy and hyperplasia.…”
mentioning
confidence: 99%
See 1 more Smart Citation